2012
DOI: 10.1371/journal.pone.0052081
|View full text |Cite|
|
Sign up to set email alerts
|

HMGB1 Is Associated with Atherosclerotic Plaque Composition and Burden in Patients with Stable Coronary Artery Disease

Abstract: ObjectivesThe role of inflammation in atherosclerosis is widely appreciated. High mobility group box 1 (HMGB1), an injury-associated molecular pattern molecule acting as a mediator of inflammation, has recently been implicated in the development of atherosclerosis. In this study, we sought to investigate the association of plasma HMGB1 with coronary plaque composition in patients with suspected or known coronary artery disease (CAD).DesignHMGB1, high sensitive troponin T (hsTnT) and high sensitive C-reactive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 43 publications
3
36
0
3
Order By: Relevance
“…HMGB1 also interacts with the receptor for advanced glycation end products or multiple TLRs and thus plays a role in inducing the release of cytokines, such as tumor necrosis factor (TNF)-a, IL-6, IL-1, and IL-8, to stimulate innate immunity. Meanwhile, Andrassy et al [18] showed that HMGB1 is related to the severity of coronary artery stenosis. These findings suggest that the release of HMGB1 plays an important role in promoting inflammation and atherogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…HMGB1 also interacts with the receptor for advanced glycation end products or multiple TLRs and thus plays a role in inducing the release of cytokines, such as tumor necrosis factor (TNF)-a, IL-6, IL-1, and IL-8, to stimulate innate immunity. Meanwhile, Andrassy et al [18] showed that HMGB1 is related to the severity of coronary artery stenosis. These findings suggest that the release of HMGB1 plays an important role in promoting inflammation and atherogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Only weak association was detected for hsCRP Blaha et al [68] hsCRP 4-sl. MDCT 6762 hsCRP was not associated with coronary artery calcification Duivenvoorden et al [70] hsCRP, MPO, and others 18 FDG-PET/CT 130 MPO levels are associated with carotid plaque inflammation Andrassy et al [62] HMBG-1 256-sl. MDCT 152 HMBG1 is associated with the composition and extend of atherosclerotic plaques Nakazato et al [64] LDL, HDL, TC ≥ 64-sl.…”
Section: Resultsmentioning
confidence: 97%
“…In an experimental setting, high mobility group box 1 (HMBG1) protein was found to be a critical mediator of acute ischemic injury, predicting adverse outcomes after myocardial infarction [60,61] . In addition, we could show that HMBG1 serum levels are associated with coronary calcification and with non-calcified plaque composition in patients with suspected or known stable CAD [62] . Incorporation of ox-LDL transforms macrophages into foam cells, which built the core of atherosclerotic plaques.…”
Section: Referencesmentioning
confidence: 89%
“…The hs-TnT was measured by the electrochemiluminescence method (ECLIA; Elecsys 2010 analyzer). Details of the test principle have been described before (54). For a quantitative determination of HMGB1 protein in serum/plasma, a highsensitivity sandwich ELISA (Shino-Test) was performed according to the manufacturer's instructions (55).…”
Section: Methodsmentioning
confidence: 99%